Quality appraisal of clinical practice guidelines for motor neuron diseases or related disorders using the AGREE II instrument - Ou, Jia-Yin; Liu, Jun-Jun; Xu, Jing; Li, Jia-Yu; Liu, Yang; Liu, You-Zhang; Lu, Li-Ming; Pan, Hua-Feng; Wang, Lin (Frontiers in Neurology, 2023)
Objectives This study aimed to systematically assess the quality of CPGs for motor neuron diseases (MNDs) or related disorders and identify the gaps that limit evidence-based practice. Methods Four scientific databases and six guideline repositories were searched for eligible CPGs. Three researchers assessed the eligible CPGs using the Appraisal of Guidelines Research and Evaluation II instrument. The distribution of the level of evidence and strength of recommendation of these CPGs were determined. The univariate regression analysis was used to explore the characteristic factors affecting the quality of CPGs. Results Fifteen CPGs met the eligibility criteria: 10 were for MND and 5 were for spinal muscular atrophy. The mean overall rating score was 44.5%, and only 3 of 15 CPGs were of high quality. The domains that achieved low mean scores were applicability (24.4%), rigor of development (39.9%), and stakeholder involvement (40.3%). Most recommendations were based on low-quality evidence and had a weak strength. The CPGs that were updated, meant for adults, and evidence based, and used a CPG quality tool and a grading system were associated with higher scores in certain specific domains and overall rating. Conclusion The overall quality of CPGs for MNDs or related disorders was poor and recommendations were largely based on low-quality evidence. Many areas still need improvement to develop high-quality CPGs, and the use of CPG quality tools should be emphasized. A great deal of research on MNDs or related disorders is still needed to fill the large evidence gap.